Evaluation of phenol chloroform DNA extraction method from a speck blood stain on cotton fabric - Nazri, Nor Amalia (2020)
In forensic casework, DNA recovery and the efficiency of DNA extraction method is one of the important key for the forensic investigator to identify the individual involved with the crime through the DNA analysis. This study therefore is intended to evaluate three parameters of phenol chloroform extraction method from a tiny blood stain on fabric cotton in order to find suitable condition that can give a high DNA recovery. Highly significant of P value suggest that the selected parameters which is the incubation time, incubation temperature and storage temperature have influenced the DNA recovery. All parameters show accepted purity value at ratio A260/A280 and very low purity value for A260/A230 in all extracted samples which may be attributed by several factors. In summary, the efficiency to dissolve DNA was found to be good when sample was stored at 56ᴼC based on the tested method.